Selected Texts from American Collections - Sollberger, E.
1. An Inscribed Statuette from the Time of Gudea — 2. An Old-Akkadian Contract — 3. A Sargonic Letter in Sumerian — 4-5. Texts Relating Ibbī-Sin’s Coronation (Emory University No. 38 and 55) — 6. gú and sa as Measures — 7-8. A Sumerian Tablet with an Akkadian Counterpart (NBC 482 and NBC 184) — 9-12. Tablets concerning Gifts of Silver Rings (HTS 143, 144, 145, 146) — 13. An Old-Babylonian School-Text.